Implementasi Penilaian pada Kurikulum Merdeka Belajar dalam Pembelajaran Sosiologi di SMAS Santun Untan Pontianak - Adhalia Zatalini (Jurnal Ilmiah Edukatif, 2023)
This research aims to review the process of assessing student learning outcomes, so that it is hoped that teachers will be able to optimize the assessment process in Sociology learning at SMAS Santun Untan Pontianak in a flexible and innovative manner. This research uses a qualitative approach with descriptive research methods, to describe the implementation of assessment in the Merdeka Curriculum in Sociology learning at SMA Santun Untan Pontianak. The data collection techniques used are observation, interview and documentation study techniques, with data collection tools in the form of observation guides, interview guides and documentation. The primary data sources in this research are Sociology teachers and several students. Based on the results of observations, interviews and documentation that researchers have carried out, it is proven that the implementation of assessment in the Merdeka Curriculum in Sociology learning at Santun Untan Pontianak High School has gone quite well. This can be demonstrated by the implementation of assessments in various forms that are adapted to each material in Sociology learning, such as formative assessments, summative assessments, and also project assessments and performance assessments to support strengthening the profile of Pancasila students. This is important to do so that educators can focus more on developing the full potential of students